2016
DOI: 10.1016/j.bbr.2015.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Altered source memory retrieval is associated with pathological doubt in obsessive–compulsive disorder

Abstract: Individuals with obsessive-compulsive disorder (OCD) often complain of doubt related to memory. As neuropsychological research has demonstrated that individuals with OCD tend to focus on details and miss the larger context, the construct of source (contextual) memory may be particularly relevant to memory complaints in OCD. Memory for object versus contextual information relies on partially distinct regions within the prefrontal cortex, parietal and medial temporal lobe, and may be differentially impacted by O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…21 They found that individuals with OCD performed equivalently in memory tasks but activated different brain regions. They concluded that activation in the posterior cingulate cortex (PCC) and the premotor/Dorsolateral prefrontal cortex (DLPFC) was associated with greater pathological doubt in their memory experiments.…”
Section: Ocd and Doubt: Empirical Studiesmentioning
confidence: 99%
“…21 They found that individuals with OCD performed equivalently in memory tasks but activated different brain regions. They concluded that activation in the posterior cingulate cortex (PCC) and the premotor/Dorsolateral prefrontal cortex (DLPFC) was associated with greater pathological doubt in their memory experiments.…”
Section: Ocd and Doubt: Empirical Studiesmentioning
confidence: 99%
“…Failures in processes associated with reality monitoring are thought to be associated with a number of psychiatric and neurological conditions (e.g., Barnes et al, 2003 ; Olson et al, 2016 ), notably including hallucinatory experiences in which an individual mistakes an internally generated mental image (e.g., inner speech; Alderson-Day and Fernyhough, 2015 ; Moseley et al, 2013 ) for an external percept ( Ditman and Kuperberg, 2005 , Jones and Fernyhough, 2007 , Seal et al, 2004 ). For example, a number of studies have shown biased performance on reality monitoring tasks in hallucinating individuals with a diagnosis of schizophrenia, compared to patients with no hallucinations, and healthy controls (e.g., Bentall et al, 1991 ; Woodward et al, 2007 ; see Brookwell et al, 2013 , for a meta-analysis).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with OCD showed abnormal activity in the temporal areas during memory performance. 15,23 Especially, memory encoding and maintenance processes are implemented through modulation of the inferior temporal activity by the prefrontal cortex. 24 Moreover, morphometric studies 13,25 revealed the differential brain volumes and thickness in ITG between OCD patients and healthy controls.…”
mentioning
confidence: 99%